Peran Organisasi Pelajar Muhammadiyah sebagai Organisasi Kaderisasi di SMA Muhammadiyah 1 Yogyakarta - Haq, Alief Yoga Dhiyaul; Ridho, Muhammad Rasyid; Mutiara, Destita (Program Pascasarjana UNU Surakarta, 2025)
This study aims to determine the role of the Muhammadiyah Student Association of Muhammadiyah 1 Yogyakarta High School (IPM Muhi) as a forum for Muhammadiyah regeneration in schools and to describe the supporting and inhibiting factors in carrying out its role. This research uses a case study approach with qualitative research methods. Data collection techniques through observation and interviews. The results of the study showed that the Muhammadiyah Student Association Branch of SMA Muhammadiyah 1 Yogyakarta has played a role as a forum for regeneration of Muhammadiyah in schools. This is realized in formal regeneration activities and non-formal regeneration. The activities are directed to 4 main themes of concentration, namely; 1) Peers, 2) Ecology, 3) Literacy, and 4) Entrepreneur. Supporting factors 1) The school provides support in the form of policies and conditioning of educators and teaching staff to participate in supporting the cadre program at school. 2) The school fully supports the funding of IPM Muhi activities. Inhibiting factors 1) low awareness of active participation by students in the activity program, 2) differences in understanding between the school and IPM Muhi administrators, 3) IPM Muhi administrators who psychologically do not fully understand their responsibilities in becoming administrators.